PENGARUH PENERAPAN MICROSOFT TEAMS TERHADAP KEMAMPUAN PEMECAHAN MASALAH SISWA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING PADA MATERI GETARAN HARMONIS - Indrawan Hermanto Abdjul; Mohamad Jahja; Abd Wahidin Nuayi; Asri Arbie (Jambura Physics Journal, 2021)
This study aims to discover the influence of the Microsoft Teams implementation on students' problem-solving ability by using a problem-based learning model on the harmonic motion topic. This research is conducted in the odd semester of the 2020/2021 academic year. This study applies the experimental method. The study takes place at SMA Negeri 1 Popayato in grade XI with research subjects are XI IPA 1 graders amounted to 20 students’ and XI IPA 3 graders amounted to 20 students. The data collection uses were the assessment of students' test results. However, the data analysis in this study uses the t-test. Based on the hypothesis test, it is obtained that  8.340 greater than  2.024 with a significance level of α = 0.05, then Ho was rejected and H1 was accepted, so it can be concluded that there is a significant effect on students' problem-solving abilities using Microsoft Teams on the Problem Based Learning model.